SIMULTANEOUS ESTIMATION OF DICLOFENAC SODIUM AND RABEPRAZOLE BY HIGH PERFORMANCE LIQIUD CHROMATOGRAPHIC METHOD IN COMBINED DOSAGE FORMS (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
A simple, accurate and reproducible HPLC method have been developed for simultaneous estimation of Diclofenac sodium and rabeprazole from their tablets formulations. A phenomenex C18 (Luna) column of length 250×7.5 mm with particle size of the stationary phase 5 µm and S mobile phase potassium dihydrogen phosphate buffer (pH adjusted to 7.5 with 1 M sodium hydroxide) and acetonitrile in the ratio 60: 40 were used in this study. Retention time was found to be 9.20 min and 6.40 min for Rabeprazole and diclofenac sodium respectively. While that for internal standard as domperidone was 11.87 min at a flow rate of 2ml / min. Linearity was found in the concentration range of 10-50 µg /ml for both the drugs in this method. The results of analysis have been validated statistically and also by recovery studies.